The Impact of Business Motivation, Business Competition, and Brand Equity on Business Development with Religiosity as Moderating Variable (Case Study MSMEs Actors in Semarang District) - Dhea Finka Audy Sukma; Ahmad Mifdlol Muthohar; Musalim Ridlo (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
This study aimed to analyze the effect of business motivation, business competition, and brand equity on business development using religiosity as a moderating variable. This study uses quantitative methods that aim to confirm the data obtained in the field with existing theories. The object of research used is the perpetrators of the Micro and Small and Medium Enterprises (MSMEs) in Semarang Regency with a sample of 100 respondents. As for the data collection technique using the questionnaire method. The data obtained were then tested using the SPSS 16 application and used multiple linear regression models and tests moderated regression analysis (MRA). The results showed that; (1) business motivation has no significant positive effect, (2) business co petition has a significant positive effect, (3) brand equity has no significant positive effect, (4) religiosity can moderate the relationship between business motivation and business development, (5) religiosity cannot moderate the relationship between business competition and business development, (6) religiosity cannot moderate the relationship between brand equity and business development